Advanced Data Encryption/Decryption using Multi Codes for One Character - Durga Prasad, R; Kiran, RNDSS; Krishnaji, Andey (International Journal of Computer Sciences and Engineering, 2025)
Cryptography is one way of providing security using the process of encryption and decryption. An original message is known as the plaintext, while the coded message is called the cipher text. The process of converting from plaintext to cipher text is known as enciphering or encryption and that of restoring the plaintext from the cipher text is deciphering or decryption. The purpose of the proposed system is to encrypt the sending message using a very sophisticated 5-codes encryption method to encrypt the data so as to ensure no leakage of sensitive and confidential information while sending a message. The proposed technique converts each character represented as a 5 codes, each code consist of a 5 digits. In order to provide advanced level of security we proposed a multi-codes generation algorithm which generates the code dynamically every time a message is initiated from either sender or receiver. The main objective of the software is to maintain the security of information transmitted via modern means of transportation such as the internet, mobile and so on. In this work, a robust RMI-based Multi Client Chat application is designed in which multiple clients can communicate through a secure RMI communication channel by sending and receiving messages between/among them. The application uses advanced encryption and decryption algorithm which uses the character codes for encryption and decryption. Each character is represented by 5 codes, each code consists of 5 digits. For example, A= 95231, 45672, 11132, 22367, 95267.